ANALISIS KESALAHAN FONEM MAHASISWA ASRAMA PUTRI KARIMUN - Junainah, Junainah; Hermandra, Hermandra; hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe Mistake of phonemes analysis was aimed at karimun ladies student dormitory. This analysis consisted of the mistake of the change of pronouncing phonemes, the mistake of addition of pronouncing phonemes, and the mistake of omission of pronouncing phonemes. The data analysis technique used is transcription, clarification, data analysis, presentation, and takes the conclusion of the mistake of phonemes. The aim of this research is to describe the mistake of the change, addition and omission of pronouncing phonemes form which dominantly done by the respondents. Based on the research done by the writer, she could conclude that the mistake of phonemes consisted of the mistake of pronouncing phonemes, the mistake of addition of pronouncing phonemes, and the mistake of omission of pronouncing phonemes which dominant from vocal and consonant phonemes form. From the analysis, the indicators of the mistake of phonemes was caused by the language change, low of understanding in bahasa Indonesia, less of teaching in bahasa Indonesia, interferential, uneven, habitual, no prior knowledge, intentional, environment, and imitation of the language which dominant used in public, and there also the components of current (trending language) language used.Key words: analysis, mistake, phonemes, Karimun ladies dormitory.